2015
DOI: 10.3390/w7094914
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration in the Nile Basin: Identifying Dynamics and Drivers, 2002–2011

Abstract: Analysis of the relationship between evapotranspiration (ET) and its natural and anthropogenic drivers is critical in water-limited basins such as the Nile. The spatiotemporal relationships of ET with rainfall and vegetation dynamics in the Nile Basin during 2002-2011 were analyzed using satellite-derived data. Non-parametric statistics were used to quantify ET-rainfall interactions and trends across land cover types and subbasins. We found that 65% of the study area (2.5 million km 2 ) showed significant (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
5
8
0
Order By: Relevance
“…These results indicate that ET in the Nile basin generally decreased over the period of 35 years considered. This is in agreement with previous studies in the region [8,24,28].…”
Section: Long-term Trendssupporting
confidence: 94%
“…These results indicate that ET in the Nile basin generally decreased over the period of 35 years considered. This is in agreement with previous studies in the region [8,24,28].…”
Section: Long-term Trendssupporting
confidence: 94%
“…On the other side of SSA (i.e., in Eastern African countries especially Ethiopia, Nile Delta, and Uganda), Alemu et al (2015) observed similar negative correlations between ET and rainfall in irrigated croplands, wetlands, and forests. Moreover, from the seasonal distribution of ET over SSA (see Section 4.3), it is noted that except for the wet seasons (i.e., the April-June and July-September period), ET values are extremely low in these Sahelian countries (i.e.,…”
Section: Spatial Correlations Of Et With Twsc and Rainfallmentioning
confidence: 64%
“…In cases of flux data unavailability, the water balance method could be used or ET products could be compared with global ET products in their research area. Some researchers directly applied this product to analyze the relationships between ET variability and vegetation dynamics without validating the reliability of the product in the Nile Basin, Africa [26,27]. To further improve the estimation of ET, the uncertainty of ET SSEBopYRB in this research area should be discussed.…”
Section: Discussionmentioning
confidence: 99%